Artesunate may inhibit liver fibrosis via the FAK/Akt/β-catenin pathway in LX-2 cells - Jian Lv; Ruidan Bai; Li Wang; Jiefang Gao; Hong Zhang (BMC Pharmacology and Toxicology, 2018)
Abstract Background An increasing number of studies are investigating the effects of Chinese medicine on hepatic fibrosis, but only few studies have examined the anti-fibrogenic properties of Artesunate (ART). The aim of the present study was to explore the anti-fibrotic effects of ART on LX-2 cells, the human HSC cell line, and to determine potential molecular mechanisms via the focal adhesion kinase (FAK)/ protein kinase B (Akt)/ β-catenin pathway. Methods LX-2 cells were stimulated with different concentration of ART (0, 12.5, 25 and 50 μg/ml) for 12, 24, 48 or 72 h, their proliferation was analyzed using the Cell Counting Kit-8 (CCK-8) assay. LX-2 cells were treated with different doses of ART (0, 12.5, 25 and 50 μg/ml) for 24 h, their apoptosis was measured using flow cytometry, the levels of mRNAs encoding collagen I or α-smooth muscle actin (α-SMA) were determined using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and the levels of key proteins in the FAK/Akt/β-catenin signaling pathway were assessed by western blotting. Specific inhibitors of FAK were added to the LX-2 cells cultures to explore the potential signaling. Results Exposing LX-2 cells to ART efficiently inhibited their proliferation, significantly promoted early apoptosis in a dose-dependent manner, and markedly downregulated the mRNA expression of α-SMA and collagen I. In addition, ART, similar to FAK inhibitor PF562271 significantly inhibited the FAK/Akt/β-catenin signaling pathway by reducing the levels of phosphorylated FAK, Akt and GSK-3β. Conclusions Our present study shows that ART could regulate the proliferation, apoptosis and activation of LX-2. Meanwhile, the anti-fibrogenic mechanisms of ART was correlated with FAK/Akt/β-catenin pathway. Future research should verify and extend these findings, as well as explore other molecules and therefore serve as useful therapeutic targets.